2020
DOI: 10.3389/fpls.2020.00412
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Glutathione Protects Subcellular Compartments From Pb-Induced ROS Injury in Leaves and Roots of Upland Cotton (Gossypium hirsutum L.)

Abstract: Heavy metals-based changes in the plants and their alleviation through eco-friendly agents including reduced glutathione (GSH) have been widely studied. In the present experiment, we tested the alleviatory role of reduced glutathione (GSH) in seedlings of upland cotton cultivar, TM-1 under lead (Pb) toxicity. Plants were grown in the Hoagland solution containing Pb (0 µM), Pb (500 µM), GSH (50 µM), and GSH + Pb (50 µM + 500 µM). Lead exposure exacerbated hydrogen peroxide (H 2 O 2 ) and hydroxyl radical (OH • … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 48 publications
0
11
0
2
Order By: Relevance
“…It contains a heme moiety at the active site and converts two H 2 O 2 molecules to oxygen and water. Multiple molecular forms of CAT isozymes (monofunctional CAT or typical CAT, CAT peroxidase, pseudo-CAT, or Mn CAT) indicate their versatile role within the plant system including cotton [146,147].…”
Section: Enzymatic Antioxidants For Ros Scavengingmentioning
confidence: 99%
See 1 more Smart Citation
“…It contains a heme moiety at the active site and converts two H 2 O 2 molecules to oxygen and water. Multiple molecular forms of CAT isozymes (monofunctional CAT or typical CAT, CAT peroxidase, pseudo-CAT, or Mn CAT) indicate their versatile role within the plant system including cotton [146,147].…”
Section: Enzymatic Antioxidants For Ros Scavengingmentioning
confidence: 99%
“…Both GR and GSH are physiologically connected, and it is their differential concentration in plants that is significant for plant defense operations against oxidative stress [148]. Previously, enhanced cesium stress has been observed to upregulate GSH activity in Arabidopsis, stimulating the antioxidant system [147].…”
Section: Enzymatic Antioxidants For Ros Scavengingmentioning
confidence: 99%
“…As a result, physiological processes besides growth inhibition also occur in rice seedlings. To scavenge the higher production of MDA and H 2 O 2 , the antioxidant defense mechanism (SOD, POD, CAT, and APX) is stimulated in plants [54,55]. In a recent study, Khan et al [56] revealed that EBL significantly increased plant growth and triggered the antioxidant defense system in wheat plants against drought stress.…”
Section: Ebl Enhanced Antioxidant Activity To Mitigate Cr Toxicitymentioning
confidence: 99%
“…The exposure of Pb and Cd in roots of W. somnifera deformed the parenchyma cells before pericycle lignification, as reported earlier under Cd stress (Shah et al, 2019). The change in orientation of subcellular organelles in primary and secondary roots of cotton (Khan et al, 2020) under Pb stress and the changes in the ultrastructure of chloroplasts and nucleus due to Cd stress in rice (Daud et al, 2016) are reported earlier. The replacement of essential metals (such as calcium, zinc, and iron) by Pb and Cd hinders the functions of enzymes using a metal cofactor and is reported in a large number of studies (Aguzie et al, 2021; Fatima et al, 2020; Rizwan et al, 2017).…”
Section: Discussionmentioning
confidence: 74%